Working time at nursing workplaces in long-term care facilities - Markiewicz, Iwona; Ksykiewicz-Dorota, Anna (Polish Journal of Public Health, 2009)
Introduction. From the aspect of the structure of use of working time by nurses employed in long-term care facilities, organisational and technical conditions resulting from the specifi city of wards and methods of staff management, play an important role. The total working time of nurses consists of direct and indirect nursing, activities associated with coordination and breaks at work. Objective. The objective of the study was the determination of the structure of working time of nurses in long-term care facilities in the care of in this type of health care units. Material and methods. The study covered 266 residents of long-term care facilities: four residential care homes, one nursing home, and one chronic care ward. The research method was the measurement of working time; the technique – day-long observation and snapshot observation. A standardised tool was applied for the needs of day-long and snapshot observation.  Results. The results obtained indicate that direct nursing care in the examined long-term care facilities was 43.05% of nurses’ working time during one work shift. The minimum time of direct nursing care was 7.14%, while the maximum time – 90.0%. The remaining working time of nurse in longterm care, i.e. 56.95% was devoted to indirect nursing care, coordination, current organisation of work, and non-duty activities. Coordination and current organization of work constituted 10.18% of working time, while the non-duty activities – 16.53%, on average. Conclusions. In the general structure of working time of nurses employed in long-term care facilities, 43.03% of time was devoted to the realisation of tasks within the scope of direct nursing, whereas non-nursing activities occupied 56.95% of the total working time. Nurses in the examined long-term care facilities devoted a considerable amount of time to administrative tasks and activities not requiring nursing qualifi cations, as well as breaks and personal activities.